Psychiatric Illness Is Common in Elderly Fracture Patients. Issue 3 (March 2019) - Gitajn, Ida L.; Titus, Alexander; Mastrangelo, Sand; Ali, Shuaibu; Sparks, Michael; Jevsevar, David
Abstract : Objectives: To (1) describe the prevalence of psychiatric illness in fracture patients ≥70 years of age and (2) investigate the association between psychiatric illness and complications requiring unplanned readmission in elderly patients. Design: Retrospective cohort study. Patients/participants: One thousand one hundred eighty-six patients ≥70 years of age with surgically treated fractures and ≥1-month follow-up treated from 2012 to 2017. Intervention: None. Main outcome measure: Complication requiring unplanned readmission. Results: Forty-four percent of patients ≥70 years of age have psychiatric comorbidities, and of those, 34% had >1 diagnosis. There was a higher rate of readmission among patients with psychiatric diagnosis compared with those without psychiatric diagnosis (35% vs. 21%, P < 0.001). There was a higher prevalence of psychiatric illness among patients 70 years of age or older compared with patients less than 70 years of age (44% vs. 39%, P = 0.007). Multivariate regression analysis controlling for age, sex, Charlson Comorbidity Index, dementia, delirium during admission, tobacco use, substance abuse, Injury Severity Score, fracture location, number of procedures, and number of fractures demonstrated an independent association between psychiatric illness and unplanned readmission (adjusted OR 1.54, 95% confidence interval, 1.15–2.07, P = 0.003). Conclusions: Almost half of the elderly patients in the present cohort have psychiatric comorbidities. Furthermore, psychiatric illness is an independent predictor of unplanned readmission, which may have substantial consequences for recovery and cost of care. This emphasizes the need for more attention to these issues in geriatric patient populations and the need to identify means to influence the downstream consequences of these comorbidities. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.